Physiological behavior of olive (Olea europaea L.) varieties under different foliage nutrition and irrigation regimes in the hyper-arid zone - Sherif El-Gioushy; Ibrahim Dobiea; Botir Khaitov; Aziz Karimov; Reda Zewail (Eurasian Journal of Soil Science, 2021)
Olive (Olea europaea) is an emblematic tree in the Mediterranean regions that grows an integral part of the area. The Mediterranean vegetation often undergoes challenging periods of severe drought stress, which causes significant impairment to olive trees' growth and production performance. The practical study was designed to follow up the effect of three irrigation regimes (50%, 75% and 100% ETc) in combination with four doses (0, 2, 4 and 6 g/L) of Lithovit (CaCO3+MgCO3, micronized calcium carbonate) on growth performance, yield, and fruit quality of two olive (Picual and Manzanello) varieties during 2017 and 2018 growing seasons. Regardless Lithovit doses, irrigation regime 100% of ETc exhibited the highest values of leaf water content, leaf relative water content, total chlorophyll and N, P, K, Ca and Mg concentrations of both olive varieties compared to the other watering regimes. Interestingly, proline content in the fruit was enhanced with increasing water deficit (50% of ETc) and Lithovit dose (6 g/L). However, the highest yield and fruit oil content were obtained by the combination of 75% ETc irrigation level and Lithovit treatment at a rate of 4 g/L in both olive varieties. This study contributes to developing olive production technologies, thereby ensuring sustainable olive culture farming with high-quality yield in hyper-arid zones.